The Effect of Age, Accommodation, and Refractive Error on the Adult Human Eye - Richdale, Kathryn; Bullimore, Mark A; Sinnott, Loraine T; Zadnik, Karla (Optometry and vision science, 2016)
To quantify changes in ocular dimensions associated with age, refractive error, and accommodative response, in vivo, in 30- to 50-year-old human subjects. The right eyes of 91 adults were examined using ultrasonography, phakometry, keratometry, pachymetry, interferometry, anterior segment optical coherence tomography, and high-resolution magnetic resonance imaging. Accommodation was measured subjectively with a push-up test and objectively using open-field autorefraction. Regression analyses were used to assess differences in ocular parameters with age, refractive error, and accommodation. With age, crystalline lens thickness increased (0.03 mm/yr), anterior lens curvature steepened (0.11 mm/yr), anterior chamber depth decreased (0.02 mm/yr), and lens equivalent refractive index decreased (0.001/yr) (all p < 0.01). With increasing myopia, there were significant increases in axial length (0.37 mm/D), vitreous chamber depth (0.34 mm/D), vitreous chamber height (0.09 mm/D), and ciliary muscle ring diameter (0.10 mm/D) (all p < 0.05). Increasing myopia was also associated with steepening of both the cornea (0.16 mm/D) and anterior lens surface (0.011 mm/D) (both p < 0.04). With accommodation, the ciliary muscle ring diameter decreased (0.08 mm/D) and the muscle thinned posteriorly (0.008 mm/D), allowing the lens to shorten equatorially (0.07 mm/D) and thicken axially (0.06 mm/D) (all p < 0.03). Refractive error is significantly correlated with not only the axial dimensions but also the anterior equatorial dimension of the adult eye. Further testing and development of accommodating intraocular lenses should account for differences in patients' preoperative refractive error.